Analyzing the Research Trend of Vitiligo in Dermatology From 1963 until 2023: A Bibliometric Analysis - Kinanti, Hapsari (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Vitiligo is one of the most common skin pigmentation disorders, which could significantly impact the possessor’s quality of life. Scholars have devoted considerable effort to advance the understanding of vitiligo but until now the treatment modalities often fall into a suboptimal condition. There are abundance of scientific updates which challenges healthcare providers to catch up with all the vast knowledge. Objective: This study aims to provide a global picture of vitiligo research and the trend of vitiligo research. Methods: This study was a bibliometric analysis study that used Scopus as the primary article database. A total of 1374 articles were analyzed using VOSviewer and Biblioshiny. Result: There was an increasing number of vitiligo articles published annually from 1963 until 2023. The most productive counties were United States of America, India, and the United Kingdom. There were four major global vitiligo research topics including epidemiology, psychology, conventional treatment, and advanced treatment. Evaluating the psychological aspects of vitiligo patients using DLQI (Dermatological Life Quality Index) is one of the recent research topics. The treatment for vitiligo shifting towards on targeting specific molecular, such as biological agents and janus kinase inhibitors. Understanding the pathogenesis of vitiligo is needed to find a better treatment modality that is specific, effective, and has minimum adverse effects. Conclusion: Current global research efforts in vitiligo shifting towards the modality of treatment that targeting specific molecular based on the pathogenesis, with also encompassing the management psychological aspect to ensure better quality of life of the possessors.